Plan estratégico para el desarrollo comunitario del recinto El Descanso sector Represa BABA de la parroquia Patricia Pilar, año 2015 - Rivera Sarzoza, Alex Vicente (2016)
The research project addressed a "Strategic Plan for Community Development in Complex" El Descanso "Baba dam area of the parish Patricia Pilar, 2015". Through internal and external situation analysis it was allowed to determine the problems in the town, where it was confirmed that there was no strategic plan to improve services and community needs. The work points out basic theories and concepts found in books by different authors and linked to strategic planning that helped in the development of research. By identifying the methods, types and techniques, along with the characterization of the target population and the respective reference sample, factors that allowed for field research, which once made it possible to determine the unmet need of the population on objectives strategic for their development and have special health center for care of their basic needs for the community and the environment. The importance of establishing the vision and mission should have the grounds to let you know that is needed for development and effective organization, in order to establish better future, by implementing strategic tools based on determined the objectives and goals of the research. The establishment of the strategic plan on the premises "The Rest" was a great opportunity for the community, given that you will satisfy many unmet needs, including those of having a health center, among other purposes that aspire to achieve from the research project. It will be of great importance in making decisions by the agencies involved in the development of rural communities in the country and to implement the Good Life of people, especially in sectors as forgotten as are the rural communities in Ecuador.